2022
DOI: 10.3390/md20090571
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nematocyst Discharge from Pelagia noctiluca (Cnidaria: Scyphozoa)—Prevention Measures against Jellyfish Stings

Abstract: Pelagia noctiluca stings are common in Mediterranean coastal areas and, although the venom is non-lethal, they are painful. Due to its high toxicity and abundance, P. noctiluca is considered a target species for the focus of research on active ingredients to reduce the symptoms of its sting. To determine the effect of 31 substances and formulations on nematocyst discharge, we performed three tests: (1) screening of per se discharge activator solutions, (2) inhibitory test with nematocyst chemical stimulation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…In the present research, scented ammonia was also considered an activator solution for R. pulmo (Figure 1D and Table 1), in agreement with the findings of Birsa et al (2010) [25] for C. quinquercirrha. In contrast, unfired nematocysts were observed after the application of urine (Figure 1G), as reported in previous research [25,35]. Our results are in contrast to those of Doyle et al (2017) [21] in C. capillata; therefore, in order to clarify the role of urine, further research with other scyphozoan species is needed.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In the present research, scented ammonia was also considered an activator solution for R. pulmo (Figure 1D and Table 1), in agreement with the findings of Birsa et al (2010) [25] for C. quinquercirrha. In contrast, unfired nematocysts were observed after the application of urine (Figure 1G), as reported in previous research [25,35]. Our results are in contrast to those of Doyle et al (2017) [21] in C. capillata; therefore, in order to clarify the role of urine, further research with other scyphozoan species is needed.…”
Section: Discussionsupporting
confidence: 67%
“…In the present study, in addition to R. pulmo, the nematocysts of Aurelia sp., Cassiopea sp., and R. luteum were also activated after the application of vinegar (Figure 2D-F and Table 2). In previous studies, vinegar or acetic acid promoted discharge in scyphomedusae such as Chrysaora quinquecirrha [25], Cyanea capillata [24,34], Nemopilema nomurai [22], and P. noctiluca [23,35]. Overall, the scientific evidence contraindicates rinsing the sting area with vinegar, acetic acid, or commercial products based on these compounds for the Scyphozoa class.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some propose the application of sand or clothing to envelop the tentacles, followed by gentle wiping; however, this may induce pressure alterations that trigger tubule discharge [ 17 ]. Ballesteros et al identified ammonia, barium chloride, bleach, scented ammonia, carbonated cola, lemon juice, sodium chloride, and papain as substances capable of inducing nematocyst discharge, which should be avoided [ 47 ]. Rinsing with fresh water should also be avoided due to its lower osmotic pressure [ 16 , 48 ].…”
Section: Inhibiting Further Discharge Of Tubulesmentioning
confidence: 99%
“…A variety of chemosensory, mechanosensory and endogenous pathways regulate the depolarization of the nematocyst membrane, culminating in the discharge of the sting [8]. Different works shown that specific compounds and ions can evoke depolarizing events and induce the discharge of nematocysts [9][10][11][12][13]. Regarding P. physalis, some works have been conducted to study the discharge [14], but this organism remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%